Democratic Innovation from West Sumbawa Regency, Indonesia: Analysis of Forum YASINAN as an Instrument of Community Participation in Development - Wahyudi, Johan (Journal of Governance and Public Policy, 2024)
This article aims to explain how the Forum YASINAN, as an actualization of democratic innovation, can become an instrument of public participation in regional development in the West Sumbawa Regency. Studies have shown that the lack of public involvement in encouraging public policy and democratic political processes is a problem in developing countries, particularly at the local government level. However, this study demonstrates how local governments can solve community problems through democratic innovation. This study was conducted in West Sumbawa. This study used democratic innovation and participatory democracy as the framework for thinking by interviewing the initiators of Forum YASINAN, representatives of beneficiary communities from eight sub-districts in West Sumbawa, a literature study, and field observations. The findings indicated that Forum YASINAN, conducted by the West Sumbawa Regency Government, has become an innovation that can increase public participation in the development process. One of the innovative aspects of the YASINAN Forum is that the Regent and Deputy Regent provide an informal space for the community to evaluate public services. It simultaneously encourages community participation as demos in which they can voice their aspirations to control the government through informal channels. The forum, which is held every week in turn in each sub-district, shows the local government’s strong willingness to encourage public participation. This study contributes by showing how governments can solve community problems through democratic innovation in the case of the West Sumbawa Regency.